Building a Digital Society: Questions for Communication Researchers - Middleton, Catherine (Journal of Telecommunications and the Digital Economy, 2014)
This paper outlines three areas in which communication researchers can offer insights on the ongoing development of a digital society: infrastructure development, the role of mobile connectivity, and the need for better data through which to understand access to, and engagement in, digital society. The paper offers a discussion of digital society, then outlines a variety of research questions that can be explored to help shape digital society in citizen-centric ways. It concludes by noting the value of research as a means of introducing alternative perspectives to discourses about digital society.